Peningkatan World Class Maintenance Score Berdasarkan Standard Assessment di PT X - Hartono, Debby; Panjaitan, Togar W.S; Bendatu, Liem Yenny (Jurnal Titra, 2013)
There are a lot of companies want to transform theirselves to be a âWorld Class Manufacturerâ. Therefore, the World Class Maintenance (WCM) concept which refers to the best practice for maintenance system is widely adopted by several companies. WCM is a structured dan systematic concept of maintenance system. It has 5 main pillars which are EARM (Equipment Availability, Reliability, and Availability), planning and scheduling, maintenance management, material management, and contracted services. Those five pillars must be well applied in the company in order to achieve a high WCM score when being audited by auditor. PT X is one of the company who has applied WCM concept in itsÂ maintenance system. The company has been assessed on WCM periodically and it has the pre-determined target. The standard assessment which has been determined is used to evaluate the WCM concept in PT X. Such improvements related to WCM has been done in order to be well applied in maintenance system and achieve a high score according to the target. WCM score from audit simulation is 4.17. It shows that the improvements which has been done give an impact on WCM score enhancement.